2023
DOI: 10.3390/nu15030634
|View full text |Cite
|
Sign up to set email alerts
|

miRNAs and Alzheimer’s Disease: Exploring the Role of Inflammation and Vitamin E in an Old-Age Population

Abstract: Alzheimer’s disease (AD) is the most frequent cause of dementia worldwide and represents one of the leading factors for severe disability in older persons. Although its etiology is not fully known yet, AD may develop due to multiple factors, including inflammation and oxidative stress, conditions where microRNAs (miRNAs) seem to play a pivotal role as a molecular switch. All these aspects may be modulated by nutritional factors. Among them, vitamin E has been widely studied in AD, given the plausibility of its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
1
2
0
2
Order By: Relevance
“…It is found that IL-17 is increased in APP/PS1 mice and Aβ-induced model mice and leads to neurotoxicity and cognitive decline through the IL-17/TRAF6/NF-κB pathway ( 53 ). However, the researchers found that the production of IL-17 in the 5xFAD mice decreased ( 54 ), and the level of IL-17 is also lower in AD patients ( 55 ), which is consistent with our research results. A study observed that IFN-γ levels in patients with mild and severe AD were higher than those in patients with moderate and MCI, respectively ( 56 ).…”
Section: Discussionsupporting
confidence: 92%
“…It is found that IL-17 is increased in APP/PS1 mice and Aβ-induced model mice and leads to neurotoxicity and cognitive decline through the IL-17/TRAF6/NF-κB pathway ( 53 ). However, the researchers found that the production of IL-17 in the 5xFAD mice decreased ( 54 ), and the level of IL-17 is also lower in AD patients ( 55 ), which is consistent with our research results. A study observed that IFN-γ levels in patients with mild and severe AD were higher than those in patients with moderate and MCI, respectively ( 56 ).…”
Section: Discussionsupporting
confidence: 92%
“…From AD patient blood samples, AD showed downregulation of miR-9, miR-21, miR29-b, miR-122, and miR-132 compared to controls. Among these, miR-122 was positively and significantly correlated with several inflammatory factors including granulocyte-macrophage colony-stimulating factor (GM-CSF), INF-a2, IL-1a, IL-8, and major intrinsic protein-1p (MIP-1p) [ 65 ]. Moreover, in AD patient blood samples, miR-1908 levels were upregulated, but ApoE levels were reduced.…”
Section: Mirna Regulation In Microglia and Macrophages In Gbm And Admentioning
confidence: 99%
“…Among patients with AD, upregulated levels of inflammatory markers and AD risk genes in association with innate immune functions have been unveiled, suggesting a prominent role of inflammation in the pathogenesis of AD [174]. The inflammatory process includes the activation of microglia and the production of pro-inflammatory cytokines [175]. Notably, microglial activation has been proven to be a vital factor linking the deleterious effects of Aβ to tau spread [176].…”
Section: Mirna-mediated Modulation Of Inflammation In Admentioning
confidence: 99%